YsbA and LytST are essential for pyruvate utilization in Bacillus subtilis. (9th August 2016) - van den Esker, Marielle H.; Kovács, Ákos T.; Kuipers, Oscar P.
Summary: The genome of Bacillus subtilis encodes homologues of the Cid/Lrg network. In other bacterial species, this network consists of holin‐ and antiholin‐like proteins that regulate cell death by controlling murein hydrolase activity. The YsbA protein of B. subtilis is currently annotated as a putative antiholin‐like protein that possibly impedes cell death, whereas YwbH is thought to act as holin‐like protein. However, the actual functions of YsbA and YwbH in B. subtilis have never been characterized. Therefore, we examined the impact of these proteins on growth and cell death in B. subtilis . We did not find a connection to the regulation of programmed cell death, but instead, our experiments reveal that YsbA and its two‐component regulator LytST are essential for growth on pyruvate. Moreover, deletion of ysbA and lytS significantly reduces pyruvate consumption. Our findings suggest that LytST induces ysbA transcription in the presence of pyruvate, and that YsbA is involved in pyruvate utilization presumably by functioning as pyruvate uptake system. We show that B. subtilis excretes pyruvate as overflow metabolite in rich medium, indicating that pyruvate could be a common nutrient in the environment. Hence, YsbA and LytST might play a major role in environmental growth of B. subtilis .